LINGUODIDACTIC BASES OF TEACHING ENGLISH - Mamedova Madina Ashuralievna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the theoretical foundations of linguodidactics of teaching a foreign language and the formation of competence in foreign language professionally-oriented communication. It also describes professional competencies formed by means of a foreign language and methodological approaches to teaching, dwelling in detail on the tasks that need to be solved to develop a high-quality methodological model of teaching a foreign language.